2018
DOI: 10.1111/epi.14533
|View full text |Cite
|
Sign up to set email alerts
|

Decreased vesicular acetylcholine transporter related to memory deficits in epilepsy: A [18F] VAT positron emission tomography brain imaging study

Abstract: [ F] VAT PET is a promising method to test the level of VAChT as a valuable biomarker for memory deficits in pilocarpine-induced chronic epileptic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Disruption of this activity through pathological processes (e.g., the generation of epileptic spikes) may be a significant mechanism underlying the pathogenesis and cognitive deficits in epilepsy. Centres in China have engaged in research in this field and some pioneering findings have been reported [82][83][84][85][86][87][88][89][90] . Temporal lobe epilepsy (TLE) with hippocampal sclerosis is the most common type of drug-resistant epilepsy.…”
Section: Epilepsy Researchmentioning
confidence: 99%
“…Disruption of this activity through pathological processes (e.g., the generation of epileptic spikes) may be a significant mechanism underlying the pathogenesis and cognitive deficits in epilepsy. Centres in China have engaged in research in this field and some pioneering findings have been reported [82][83][84][85][86][87][88][89][90] . Temporal lobe epilepsy (TLE) with hippocampal sclerosis is the most common type of drug-resistant epilepsy.…”
Section: Epilepsy Researchmentioning
confidence: 99%
“…Schildt et al suggested that the discrepancy between raclopride and haloperidol pre-treatment effects was due to haloperidol blockade of off-target [ 18 F]­FEOBV binding to σ receptors. This seems unlikely as brain [ 18 F]­FEOBV uptake is not affected by pre-treatment with the σ antagonist (+)-3-PPP, the strong concordance between regional distribution of [ 18 F]­FEOBV binding revealed in human PET studies and prior post-mortem based characterizations of the organization of human brain cholinergic systems, and results of rodent lesion experiments correlating ex vivo measurements of cholinergic systems integrity with in vivo [ 18 F]­FEOBV and [ 18 F]­VAT PET measurements. In addition, FEOBV has a low affinity for the human σ 1 receptor…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of VAChT expression has consequences on the concentration of acetylcholine loaded in the secretory vehicle, thus indirectly maintaining the neurotransmitter release. Dysregulation of VAChT has been reported in several diseases like AD, Epilepsy, and Sepsis (117)(118)(119). VAChT knockdown (VAChT-KD) mice, upon LPS challenge, show increased susceptibility to inflammation and greater mortality.…”
Section: Rivastigminementioning
confidence: 99%